A locally compact quantum group of triangular matrices - Fima, P.; Vainerman, L. (Український математичний журнал, 2008)
We construct a one parameter deformation of the group of 2×2 upper triangular matrices with determinant
1 using the twisting construction. An interesting feature of this new example of a locally compact quantum
group is that the Haar measure is deformed in a non-trivial way. Also, we give a complete description of
the dual C∗-algebra and the dual comultiplication. Побудовано однопараметричну деформацію групи верхніх трикутних матриць розміру 2 × 2 із детермінантом 1 з використанням конструкції скруту. Цікавою рисою цього нового прикладу локально компактної квантової групи є нетривіальна деформація міри Хаара. Наведено також повний опис дуальної C*-алгебри та дуальної комультиплікації.